Produção de material didático para ensino da gravitação aplicado à tecnologia dos lançamentos de satélites - Carvalho, Andréa Amaral Santos (2020)
The present work shows how a set of interdisciplinary activities involving the areas of Astronomy and Gravitation was developed with a particular focus on the era of artificial satellites and rockets, addressing, some technological applications for the benefit and development of society. However, to explore as much ideas and interdisciplinary content as possible, activities were developed and carried out in partnership with the teachers of Mathematics, History, Portuguese, English and Chemistry of the Centro Integrado de Educação Assis Chateaubriand, contemplating the production of videos, interpretation and production of texts, construction of models and rockets involving physical, geometric and mathematical aspects, manufacture of illustrative panels, banners with images produced by rockets and artificial satellites (of the planets: Earth and Mars) as well as experiments that allowed contextualizing elements of Astronomy and Gravitation in the classroom in a playful, interactive and dynamic way. The educational product, linked to this dissertation, is a Manual for Teaching Astronomy and Gravitation, which brought together some interdisciplinary experiences developed with the objective of serving as a didactic support material for the various disciplines discussed previously.